Sustainable Production of African Traditional Beers With Focus on Dolo, a West African Sorghum-Based Alcoholic Beverage - Sawadogo-Lingani, Hagrétou; Owusu-Kwarteng, James; Glover, Richard; Diawara, Bréhima; Jakobsen, Mogens; Jespersen, Lene (Frontiers in Sustainable Food Systems, 2021)
Spontaneously fermented sorghum beers remain by far the most popular traditional cereal-based alcoholic beverages in Africa. Known under various common names (traditional beers, sorghum beers, opaque, native or indigenous beers) they are also recognized under various local names depending on the region or ethnic group. Dolo and pito are two similar traditional beers popular in West African countries including Burkina Faso, Mali, Ghana, Benin, Togo, Nigeria and Ivory Coast. These low-alcoholic beers are nutritious and contribute to the nutritional balance of local populations, as well as to their socio-cultural and economic well-being. The production of African traditional beers remains one of the major economic activities, creating employment and generating substantial income that contributes to livelihoods as well as the countries' economic systems. Their processing (malting and brewing) is still artisanal, based on traditional family know-how. The brewing process involves either an acidification and an alcoholic fermentation phases, or a mixed fermentation combining LAB and yeasts. Saccharomyces cerevisiae has been identified as the dominant yeast species involved in the alcoholic fermentation, with a biodiversity at strain level. LAB involved in the processing belong to the genera of Limosilactobacillus, Lactobacillus, Pediococcus, Leuconostoc, Lactococcus, Streptococcus, and Enterococcus. Molds (Aspergillus, Penicillium, Rhizopus, Geotrichum), and acetic bacteria are often associated with the malting and brewing processes. Challenges for sustainable production of African sorghum beer include inconsistent supply of raw materials, variability in product quality and safety, high energy consumption and its impact on the environment, poor packaging and short shelf-life. For sustainable and environmentally-friendly production of African sorghum beers, there is the need to assess the processing methods and address sustainability challenges. Strategies should promote wider distribution and adoption of improved sorghum varieties among farmers, prevent losses through the adoption of good storage practices of raw material, promote the adoption of improved cook stoves by the brewers, develop and adopt starter cultures for controlled fermentation, regulate the production through the establishment of quality standards and better valorize by-products and wastes to increase the competitiveness of the value chain. Appropriate packaging and stabilization processes should be developed to extend the shelf-life and diversify the channels for sustainable distribution of African cereal-based alcoholic beverages.